Deciphering the regulatory code driving neural crest evolution and development - Prag, Mayur (Department of Human Biology, 2022)
Neural crest cells are a unique feature of vertebrates. This embryonic cell population is multipotent, giving rise to many structures including peripheral neurons. The sea lamprey, Petromyzon marinus, is at the base of the vertebrate lineage and offers an ideal model for the ancestral neural crest. Comparisons to the modern neural crest gene regulatory network (GRN) such as that of the chicken can elucidate essential conserved regions of the GRN. Previous studies in P. marinus revealed a neural crest-specific enhancer for the neural crest specification gene, SoxE1, which showed conserved activity in chicken and zebrafish neural crest. Here, the SoxE1 enhancer was subdivided to find the core active region, using enhancer-reporter assays in chicken and lamprey. Additionally, the segments were analysed for putative transcription factor binding sites, which were mutated. The central 610 bp of the SoxE1 enhancer retained its activity in lamprey and chicken neural crest. Mutation of a putative Sox10 and Tfap2 binding sites within the core enhancer did not result in complete loss of enhancer activity in the chicken or lamprey, however the number of positive embryos was reduced in the lamprey. Further subdivision of the SoxE1 enhancer core region revealed the 3' half drives expression in the branchial arches of the chicken embryo. Neural crest specific-reporter activity was confirmed by immunological staining embryo sections with the reporter gene overlapping with neuronal and endogenous Sox10 expression. The identified core region of the SoxE1 enhancer shows a conserved regulatory mechanism in vertebrates. Future work will interrogate how this enhancer region interacts directly with neural crest GRN members. In addition, preliminary single cell RNA-seq analysis of dissected dorsal neural tube tissue from the lamprey embryos revealed a neural crest specific cell population that expressed key neural crest specification marker genes. This data can reveal previously unknown genes involved in the neural crest GRN as well as identifying novel cell types during development.